Glycopyrronium once-daily significantly improves lung function and health status when combined with salmeterol/fluticasone in patients with COPD: the GLISTEN study—a randomised controlled trial - Peter Frith; Philip J. Thompson; Rajeev Ratnavadivel; Catherina L. Chang; Peter Bremner; Peter Day; Christina Frenzel; Nicol Kurstjens (2015)
Background The optimal use of various therapeutic combinations for moderate/severe chronic obstructive pulmonary disease (COPD) is unclear. The GLISTEN trial compared the efficacy of two long-acting anti-muscarinic antagonists (LAMA), when combined with an inhaled corticosteroid (ICS) and a long-acting β2 agonist (LABA). Methods This randomised, blinded, placebo-controlled trial in moderate/severe COPD patients compared once-daily glycopyrronium (GLY) 50 µg, once-daily tiotropium (TIO) 18 µg or placebo (PLA), when combined with salmeterol/fluticasone propionate (SAL/FP) 50/500 µg twice daily. The primary objective was to determine the non-inferiority of GLY+SAL/FP versus TIO+SAL/FP on trough FEV1 after 12 weeks. An important secondary objective was whether addition of GLY to SAL/FP was better than SAL/FP alone. Results 773 patients (mean FEV1 57.2% predicted) were randomised; 84.9% completed the trial. At week 12, GLY+SAL/FP demonstrated non-inferiority to TIO+SAL/FP for trough FEV1: least square mean treatment difference (LSMdiff) −7 mL (SE 17.4) with a lower limit for non-inferiority of −60 mL. There was significant increase in week 12 trough FEV1 with GLY+SAL/FP versus PLA+SAL/FP (LSMdiff 101 mL, p<0.001). At 12 weeks, GLY+SAL/FP produced significant improvement in St George9s Respiratory Questionnaire total score versus PLA+SAL/FP (LSMdiff −2.154, p=0.02). GLY+SAL/FP demonstrated significant rescue medication reduction versus PLA+SAL/FP (LSMdiff −0.72 puffs/day, p<0.001). Serious adverse events were similar for GLY+SAL/FP, TIO+SAL/FP and PLA+SAL/FP with an incidence of 5.8%, 8.5% and 5.8%, respectively. Conclusions GLY+SAL/FP showed comparable improvements in lung function, health status and rescue medication to TIO+SAL/FP. Importantly, addition of GLY to SAL/FP demonstrated significant improvements in lung function, health status and rescue medication compared to SAL/FP. Trial registration number NCT01513460.